2013
DOI: 10.14260/jemds/248
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic Restorative Treatment –A Review

Abstract: Atraumatic Restorative Treatment (ART) was originally developed in field settings in African subcontinent (Tanzania) by University of Dar el Salaam in 1980s; subsequently World Health Organization (WHO) promotes the use of ART especially with children. As the name indicates Atraumatic Restorative Treatment (ART) is basically a minimally invasive procedure that involves removing of softened carious dentine using hand instruments and then restoring the cavity with an adhesive material usually the Glass Ionomer C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Black stated his vision for the future of dentistry as follows: "The day is surely coming and perhaps within the lifetime of you young men before me when we will be engaged in practicing preventive rather than reparative dentistry". Sajjanshetty, et al reported that the survival rates of ART restorations were similar or superior to mercury dental amalgam after 6 years [84,85].…”
Section: Shift In Dentistrymentioning
confidence: 99%
“…Black stated his vision for the future of dentistry as follows: "The day is surely coming and perhaps within the lifetime of you young men before me when we will be engaged in practicing preventive rather than reparative dentistry". Sajjanshetty, et al reported that the survival rates of ART restorations were similar or superior to mercury dental amalgam after 6 years [84,85].…”
Section: Shift In Dentistrymentioning
confidence: 99%
“…Black stated his vision for the future of dentistry as follows: "The day is surely coming and perhaps within the lifetime of you young men before me when we will be engaged in practicing preventive rather than reparative dentistry". Sajjanshetty, et al reported that the survival rates of ART restorations were similar or superior to mercury dental amalgam after 6 years [84,85].…”
Section: Shift In Dentistrymentioning
confidence: 99%